(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
With the constitutional reform of 2022, ’future generations’ make their appearance in the Italian Constitutional text. The reference to future generations had already been developed by the Constitutional Court, founding this reference in the Constitutional Law No. 1/2012 to implement the sound management of public finances, together with the related principle of ’political responsibility’ in the exercise of elective office. Comparing the two constitutional revisions, the essay aims to reflect on the existence and implications of a principle of an objective political responsibility towards the new generations in respect of the new ecological purposes included in the Constitution.